DAMPAK DESENTRALISASI FISKAL TERHADAP KINERJA EKONOMI DAERAH - Shofwatun Hasna (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2015)
This study aims to analyze the fiscal decentralization impact to economic performance in Province of East Java for five years (2009-2013). The panel model closen is random effect. The East Java income is growing up each year during 2009 until 2013. The target and realization of Regional Expenditure is also growing up in that periode even not used 100%. The analysis result shows that revenue Sharing Fund (DBH), Miscellaneous Local Revenues, and Local Government Revenue (PAD) have positive impact to economic activities in East Java During that period, but Special Alocation Funds (DAK) and General Allocation Funds(DAU) have no impact during research periode.